TARGET AND LEARNING NEEDS IN ENGLISH FOR MIDWIFERY STUDENTS - Diyah Nur Hidayati; Sri Haryati (UIN Raden Mas Said Surakarta, 2018)
Teaching English for midwifery students is categorized as English for Specific Purposes (ESP). In this course, need analysis need to be conducted to discover what students already know, what they need to know, and what they want to know. To this end, the study investigated the target needs and learning needs of midwifery students. A total of 53 students responded to a questionnaire and open-ended interview. The results demonstrated that students wanted to be able to communicate English fluently. Also, they wanted to understand various English texts related to their midwifery field. The result also showed that most students were at the beginner level indicating that they were just able to understand simple sentences and expressions used in a daily life. Regarding learning needs, students preferred to have the input text in the form of dialogue and monologue provided with pictures with the length of the texts of less than 150 words and between 150-250 words. According to the results obtained from this study, it can be concluded that need analysis needs to be conducted before giving the English course based on the students’ field study.